Long-Term Outcomes of Endovascular Aneurysm Repair. Can We Reckon upon a Long-Term Result? - Furkalo, S.; Nikulnikov, P.; Khasyanova, I.; Vlasenko, E. (Ukrainian Journal of Cardiovascular Surgery, 2019)
This article represents the analysis of the long-term outcomes of endovascular treatment of infrarenal aortic aneurysms in 110 patients who underwent endovascular aneurysm repair (EVAR). The age of the patients was 68.5 ± 9.8 years, 104 patients were males. Hypertension was noted in the absolute majority – 101 patients, which accounted for 92 % of cases. Concomitant coronary heart disease (CHD) was diagnosed in 83 patients (75.3 %), and grade II–III stable angina was noted in 65% of the patients. Forty five (41 %) patients had a history of myocardial infarction. Type II diabetes mellitus was reported in 7 (6.3 %) patients. Previously, 26 (23.6 %) patients had myocardial revascularization. Four (3.6 %) patients had aortic valve stenosis. In most cases – 91 (82.7 %) – the clinical course of the underlying disease was asymptomatic and oligosymptomatic. The main indicators of EVAR long-term effectiveness are the absence of aneurysm rupture and aneurysmal sac reduction. Statistical analysis showed stable and reliable relationship between the nature of morphological changes in the femoral artery wall and changes in the size of aneurysmal sac after EVAR. As for atherosclerotic changes, predominant aneurysmal sac reduction was observed in 77.7 % of cases, and only in 28.7 % of cases with dystrophic changes. Patients undergoing EVAR require long-term regular follow-up using the methods like ultrasound and computerized tomography. Monitoring of the changes in the aneurysmal sac size, detection of endoleaks and timely correction of the latter, if necessary, ensure long-term effectiveness of the intervention.